Homelessness & Health in Canada - Manal Guirguis-Younger (Les Presses de l'Université d'Ottawa | University of Ottawa Press, 2014)
Homelessness & Health in Canada explores, for the first time, the social, structural, and environmental factors that shape the health of homeless persons in Canada. Covering a wide range of topics from youth homelessness to end-of-life care, the authors strive to outline policy and practice recommendations to respond to the ongoing public health crisis. This book is divided into three distinct but complimentary sections. In the first section, contributors explore how homelessness affects the health of particular homeless populations, focusing on the experiences of homeless youth, immigrants, refugees and people of Aboriginal ancestry. In the second section, contributors investigate how housing and public health policy as well as programmatic responses can address various health challenges, including severe mental illness and HIV/AIDS. In the final section, contributors highlight innovative Canadian interventions that have shown great promise in the field. Together, they form a comprehensive survey of an all too important topic and serve as a blueprint for action.